2011
DOI: 10.1093/ndt/gfr502
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgical complications following simultaneous pancreas-kidney transplantation

Abstract: Surgical complications following SPK transplantation can cause significant morbidity and adversely affect pancreas graft survival, but do not affect long-term kidney or patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 36 publications
2
59
1
Order By: Relevance
“…Previous studies have shown that SPKT recipients with early technical failure of the pancreas have significantly inferior kidney graft survival rates compared to those who did not (59.5% vs 82% at three years, P < .001) [7]. Contrary to this, Banga [8] reveals that longterm kidney survival remains unaffected in patients who experience early re-laparotomy compared to those who did not (82% versus 83%, at 5 years P ¼ .412). In our study, the survival rate of kidney grafts was lower among patients who presented with grades IIIb or IVa-b complications than those who did not have early technical failure (kidney survival rate at 5 years 81.8% vs 97.3%; P ¼ .02), showing an independent influence adjusted for immunologic and other important variables that influence postoperative complications.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies have shown that SPKT recipients with early technical failure of the pancreas have significantly inferior kidney graft survival rates compared to those who did not (59.5% vs 82% at three years, P < .001) [7]. Contrary to this, Banga [8] reveals that longterm kidney survival remains unaffected in patients who experience early re-laparotomy compared to those who did not (82% versus 83%, at 5 years P ¼ .412). In our study, the survival rate of kidney grafts was lower among patients who presented with grades IIIb or IVa-b complications than those who did not have early technical failure (kidney survival rate at 5 years 81.8% vs 97.3%; P ¼ .02), showing an independent influence adjusted for immunologic and other important variables that influence postoperative complications.…”
Section: Discussionmentioning
confidence: 91%
“…Most published articles focus on complications that require reoperation but do not use available reporting systems [8,13,14], which will allow series comparison and conclusions to be reached to avoid complications and improve patient care. To address this need, there has been an increase in the number of studies using the ClavienDindo system [15e17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that surgical complications are associated with strong non-immunologic complications after transplantation in the early postoperative period [10]. Anticoagulation therapy after SPK transplantation is also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Refinements in surgical technique and immunosuppressive therapy have considerably improved outcome; however, the complication rate remains still at about 25% [47].…”
Section: Pancreas Transplantationmentioning
confidence: 99%